Effect of nursing telemonitoring on the knowledge of obese women: clinical trial - Fernanda Carneiro Mussi; Catia Suely Palmeira; Carlos Antonio de Souza Teles Santos; Armenio Costa Guimarães; Maria de Lourdes Lima; Taise Santos do Nascimento
ABSTRACT Objective: To assess the effectiveness of remote monitoring in the knowledge of overweight women. Method: Randomized clinical trial with 101 women, randomly assigned to the control group (CG=50) and to the intervention group (IG=51). The IG received educational intervention over the telephone, during three months and routine follow-up in the service, while the CG only received conventional follow-up. The knowledge was assessed by a specific questionnaire. Data were analyzed by the Robust Linear Regression Model, adopting a statistical significance of 5%. Results: In the intragroup assessment, an increase in the correct answers with a statistically significant difference was observed only for the IG in the domains: "Concept and causes of overweight," "Complications of overweight" and "Eating habits." In the intergroup comparison, an increase in the average knowledge was verified in the same domains for the IG (p≤0.005). Conclusion: nursing telemonitoring contributed positively to the improvement of women's knowledge.